Evaluation Of The Performance Of The Department Of Industry And Trade Of Bengkulu City In The Management Of Panorama Market - Ramadhani , Putri R; Rikardo , Yanuar; Yusuarsono, Yusuarsono (Jurnal Multidisiplin, 2025)
This study aims to evaluate the performance of the Department of Industry and Trade of Bengkulu City in managing Panorama Market, one of the main trading centers in the city. The research employed a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings indicate that the Department has made several improvements, including vendor arrangement, provision of sanitation facilities, and supervision of market retribution. However, challenges remain, such as limited infrastructure, low awareness among traders regarding cleanliness, and weak coordination among related agencies. The performance evaluation reveals that planning and program implementation have been carried out but their effectiveness is not yet optimal due to budget constraints and limited human resource capacity. The study suggests strengthening coordination, increasing budget allocation, and empowering traders to achieve more efficient, transparent, and sustainable market management.